The Relationship Between The Response Time of The Family When Bringing The Patient to Hospital and Stroke Severity Patients - Farida Tampubolon, Lindawati; Ginting, Agustaria; Natalia, Natalia (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Non-infectious diseases, especially strokes, are increasing in Indonesia. The problem that occurs at this time is that there are still many families who do not know or don’t know at all about the early detection of stroke attacks. The study aims to determine the relationship between family response time in bringing stroke patients to the hospital and the severity of stroke patients at H. Adam Malik General Hospital Medan. Methods: This research is an analytic observational study with a cross-sectional design. The research population is unknown with a total sample of 35 people, where the sample is taken based on a purposive sampling technique, and data collection uses the NHISS instrument. Results: The results of the study find that the median response time value was 4.00 and the SD value is 42.33, while the median stroke patient severity is 21.00 and the SD value is 14.248. Based on Spearman's rho test results, the p-value is 0.008 < α = 0.05, meaning that there is a correlation between family response time and the severity of stroke patients. The correlation coefficient value is 0.441, which means that the faster the family's response time in bringing the patient to the hospital, the lighter the stroke patient's severity. Conclusion: It is hoped that the family will be able to carry out an initial stroke assessment at home by looking at a smile that tilts to one side, half of the body is weak and speaks pelo, and immediately takes the patient to the hospital.